Ac Stark shift in double resonance and coherent population trapping in a wall-coated cell for compact Rb atomic clocks - Miletic, Danijela; Bandi, Thejesh; Affolderbach, Christoph; Mileti, Gaetano (My University, 2012)
We present a comparative study of the light-shifts (ac Stark shift) in a Rb vapour cell using two possible schemes for Rb atomic clocks: double resonance (DR) and coherent population trapping (CPT). For both schemes, the same wall-coated cell in a compact atomic resonator was used. The light-shift resulting from a monochromatic (DR) or a non-monochromatic (CPT) optical excitation was measured as a function of the laser intensity and the laser frequency and compared with existing theoretical results